Manajemen User Interface Pada Game 2D Berbasis Finite State Machine - Hariadi, Fajar (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
User interface is very important in a game cause it manages how the player interacts with the game itself. Managing a lot of menu in the user interface is quite challenging for the developer of the game. The menu can have a lot of different function in each part of the sub-menu. So in this article, we will see how to use the Finite State Machine concept for solving the management problems